School Well-Being and Social Relationships of College Students During the COVID-19 Pandemic - Mercier, Cendrine; Florin, Agnès; Zanna, Omar; Constans, Stéphanie (Journal of the Canadian Association for Curriculum Studies, 2023)
During the period of progressive lockdown restriction easing, a self-administered online survey of subjective well-being was conducted among high college students who returned to college on May 18, 2020, and others who stayed at home. The 286 completed survey returns reflect the significant differences in the school experiences of the two groups, particularly in terms of social relations, which were affected by the principle of "social distance". The initial findings confirm the results of work already carried out on student well-being and reveal new elements to consider when measuring student subjective well-being.